STED‐TEM Correlative Microscopy Leveraging Nanodiamonds as Intracellular Dual‐Contrast Markers. Issue 5 (18th December 2017) - Prabhakar, Neeraj; Peurla, Markus; Koho, Sami; Deguchi, Takahiro; Näreoja, Tuomas; Chang, Huan‐Cheng; Rosenholm, Jessica M.; Hänninen, Pekka E.
Abstract: Development of fluorescent and electron dense markers is essential for the implementation of correlative light and electron microscopy, as dual‐contrast landmarks are required to match the details in the multimodal images. Here, a novel method for correlative microscopy that utilizes fluorescent nanodiamonds (FNDs) as dual‐contrast probes is reported. It is demonstrated how the FNDs can be used as dual‐contrast labels—and together with automatic image registration tool SuperTomo, for precise image correlation—in high‐resolution stimulated emission depletion (STED)/confocal and transmission electron microscopy (TEM) correlative microscopy experiments. It is shown how FNDs can be employed in experiments with both live and fixed cells as well as simple test samples. The fluorescence imaging can be performed either before TEM imaging or after, as the robust FNDs survive the TEM sample preparation and can be imaged with STED and other fluorescence microscopes directly on the TEM grids. Abstract : Fluorescent nanodiamonds are presented here as dual‐contrast imaging probes for intracellular correlation using super‐resolution stimulated emission depletion and transmission electron microscopy. This correlative light and electron microscopy probe is demonstrated to be suitable for live cell imaging, fixed cell imaging, and further, super‐resolution imaging.